Legalitas Penetapan Kerugian Keuangan Negara Oleh Aparat Pengawas Internal Pemerintah (APIP) Sebagai Dasar Memeriksa Perkara Korupsi - Rumihin, Maria; Eliazer Marthen, Salmon Eliazer Marthen; Hehanussa, Deassy Jacomina Anthoneta (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2023)
To prevent and eradicate criminal acts of corruption in the bureaucracy of government institutions and prevent errors and irregularities in the implementation of duties by apparatus in the government bureaucracy, the existence of the government internal supervision apparatus (APIP) is considered very important to conduct internal supervision of government apparatus in carrying out government duties. However, the authority given by law to APIP is often not in line with APH (Law Enforcement Officers) often use the results of the State loss calculation report by APIP as a basis for prosecuting someone suspected of committing a Criminal Act of Corruption. This type of research is normative juridical. The type of research is descriptive-analytical. The source of legal materials uses primary legal materials and secondary legal materials. Techniques for collecting legal materials through literature study and qualitative analysis of legal materials. The results showed that the only institution that has the authority to calculate and determine State Financial Losses is the Audit Board by attribution given by the Constitution Therefore, every charge committed by APH (Law Enforcement Officer) must be null and void or can be canceled because it is not in line with existing regulations.